2017
DOI: 10.15171/ijer.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Socioeconomic Determinants of Physical and Mental Self-rated Health Across 10 Ethnic Groups in the United States

Abstract: Background and aims: The aim of this study was to explore ethnic differences in demographic and socioeconomic determinants of poor physical and mental self-rated health (SRH) in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
0
11
1
Order By: Relevance
“…In other words, education affects health indirectly through social support. This result is not consistent with other studies [ 6 10 ] that argued a direct education effect on health. However, the significant path from education to social support and the one from social support to health were in agreement with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, education affects health indirectly through social support. This result is not consistent with other studies [ 6 10 ] that argued a direct education effect on health. However, the significant path from education to social support and the one from social support to health were in agreement with previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The health effects of education attainment against risk of morbidity and mortality are well established [ 6 8 ]. High education is shown to protect against a decline in self-rated health (SRH) [ 9 , 10 ], chronic disease [ 11 ], and mortality [ 12 ]. As another essential component of human life, social support has been known to be associated with health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for suicide and emotional problems, particularly depression, needs to consider the racial variations in experience and expression of negative emotions and cognitions [ 44 , 45 ]. Multiple studies have shown differences between Blacks and Whites in how poor self-evaluation of mental health reflects psychiatric disorders, such as depression [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…SRPH was dichotomized as poor/fair (1) and good/very good/excellent (0) and high SES was shown to predict better SRPH. 6…”
Section: Dependent Variable Self-rated Physical Health (Srph)mentioning
confidence: 99%
“…[1][2][3][4][5] High SES is also related to self-rated physical health (SRPH). 6 According to the Minorities' Diminished Return Theory, the members of race/ethnic minority groups and White Americans differ regarding the relationship between their SES and health. 7,8 The protective effects of SES on physical, mental, and oral health are also found to vary for Blacks [9][10][11][12][13][14][15][16] and Hispanics 10 compared to Whites.…”
Section: Introductionmentioning
confidence: 99%